Jabal Hafit anticline (UAE and Oman) formed by décollement folding followed by trishear fault-propagation folding. (December 2018) - Hansman, Reuben J.; Ring, Uwe
Abstract: Creating three-dimensional (3D) models to replicate geological structures is crucial in discerning the geometry and kinematics of an orogen. The Jabal Hafit anticline, in the foreland of the Al Hajar Mountains, extends through Oman and the United Arab Emirates and is a relatively simple and well exposed structure. Surprisingly, previous studies of this anticline have presented conflicting interpretations regarding the strain field and the timing of deformation. In this study a structural 3D geological model of the Jabal Hafit anticline is constructed and demonstrates that the anticlines geometry can be reproduced by a two-phase model: (1) flexural slip folding, followed by (2) trishear fault-propagation folding. The trishear mode occurred due to a west-dipping backthrust that propagated from the décollement, to accommodate WSW–directed shortening. The different geometries of the various biostratigraphic layers indicate that anticline growth occurred during the late Oligocene to early–middle Miocene. This timing supports the recently established age for uplift of the Al Hajar Mountains. Highlights: Jabal Hafit anticline formed by two-phase deformation sequence. Décollement folding followed by trishear fault-propagation folding. WSW–directed shortening occurred during the late Oligocene to early–middle Miocene. Timing of the Jabal Hafit anticline provides minimum age for the Al Hajar Mountains.